2002
DOI: 10.1080/00221300209602097
|View full text |Cite
|
Sign up to set email alerts
|

Behavioral Effects of Chronic Melatonin and Pregnenolone Injections in a Myelin Mutant Rat (taiep)

Abstract: The taiep (tremor, ataxia, immobility, epilepsy, and paralysis) myelin mutant displays a number of locomotor deficits. Taiep rat gait is characterized by shorter stride and step lengths as well as by larger stride widths. Thirty-day-old taiep mutants were placed under a regimen of daily hormone injections for 60 days. Animals in Condition 1 received melatonin, those in Condition 2 received pregnenolone sulfate, and those in a third control condition received injections of saline. Following the injections, each… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2005
2005
2015
2015

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 21 publications
(17 reference statements)
1
7
0
Order By: Relevance
“…Although the myelin sheath has traditionally not been considered critical to the pathogenesis of epilepsy, recent reports have demonstrated that CNS myelin sheaths are affected in certain epilepsy patients (Concha et al, 2009;Nilsson et al, 2008;Scanlon et al, 2013;Schoene-Bake et al, 2009), and our previous study confirmed that demyelination of the hippocampus occurs in lithium-pilocarpine-induced epileptic rats (Ye et al, 2013). In addition, epileptic seizures have also been observed in patients with multiple sclerosis, a typical demyelinating disease of the CNS, and in different animal models with myelin diseases (Anderson and Rodriguez, 2011;Bloom et al, 2002;Eguibar and Cortes Mdel, 2010). These findings indicate an association between epilepsy and abnormal myelin damage.…”
Section: Introductionmentioning
confidence: 69%
“…Although the myelin sheath has traditionally not been considered critical to the pathogenesis of epilepsy, recent reports have demonstrated that CNS myelin sheaths are affected in certain epilepsy patients (Concha et al, 2009;Nilsson et al, 2008;Scanlon et al, 2013;Schoene-Bake et al, 2009), and our previous study confirmed that demyelination of the hippocampus occurs in lithium-pilocarpine-induced epileptic rats (Ye et al, 2013). In addition, epileptic seizures have also been observed in patients with multiple sclerosis, a typical demyelinating disease of the CNS, and in different animal models with myelin diseases (Anderson and Rodriguez, 2011;Bloom et al, 2002;Eguibar and Cortes Mdel, 2010). These findings indicate an association between epilepsy and abnormal myelin damage.…”
Section: Introductionmentioning
confidence: 69%
“…For example, as already discussed, DTI abnormalities have been found in patients and animal epilepsy models (Eriksson et al, 2001;Grant, 2005;Kimiwada et al, 2006;Luat and Chugani, 2008;Obenaus and Jacobs, 2007;Rugg-Gunn et al, 2001;Rugg-Gunn et al, 2002;Thivard et al, 2005). Epileptic seizures occur in several different rodent mutants with myelin diseases (Bloom et al, 2002;Bradl et al, 1999;Griffiths, 1996;Hoffmann et al, 2008;Rosenbluth, 1990;Seyfried et al, 1986). In humans, seizures are known to occur with increased incidence in patients with multiple sclerosis (Koch et al, 2008), and infantile spasm, a form of pediatric epilepsy, has been associated with abnormal myelination (Muroi et al, 1996;Schropp et al, 1994).…”
Section: Discussionmentioning
confidence: 99%
“…For example, pregnenolone increases myelin sheath thickness following sciatic nerve cryolesion (Koenig et al, 1995). Also implicating a modulatory role for neuroactive steroids in myelination, chronic pregnenolone treatment improved locomotor behavior in myelin mutant mice (Bloom et al, 2002). DHEA treatment increases the number of myelinated fibers in rat sciatic nerve and enhances functional recovery following crush injury (Gudemez et al, 2002), and increases axonal outgrowth in vitro (Compagnone and Mellon, 1998).…”
Section: Neuroactive Steroid Alterations and Possible Ramifications Fmentioning
confidence: 99%